Genome-Wide Association Studies: Progress in Identifying Genetic Biomarkers in Common, Complex Diseases - Stephen F. Kingsmore; Ingrid E. Lindquist; Joann Mudge; William D. Beavis (Biomarker Insights, 2007)
Novel, comprehensive approaches for biomarker discovery and validation are urgently needed. One particular area of methodologic need is for discovery of novel genetic biomarkers in complex diseases and traits. Here, we review recent successes in the use of genome wide association (GWA) approaches to identify genetic biomarkers in common human diseases and traits. Such studies are yielding initial insights into the allelic architecture of complex traits. In general, it appears that complex diseases are associated with many common polymorphisms, implying profound genetic heterogeneity between affected individuals.